0417 Odds Ratio Product reveals distinct sleep phenotypes in idiopathic hypersomnia. (25th May 2022) - Thomas, Robert; Gerardy, Bethany; Blattner, Margaret; Younes, Magdy
Abstract: Introduction: The pathophysiology of idiopathic hypersomnia with long sleep times (IH) remains an enigma. Alternate methods to characterize sleep such as the Odds Ratio Product (ORP), a continuous measure of sleep depth, has the potential to improve understanding of IH. Methods: The Odds ratio product is a continuous measure of sleep depth and propensity ranging 0 (very deep sleep) to 2.5 (Least sleep propensity). The difference between 2.5 and ORP in any epoch indicates extent of wake suppression (sleep depth) for that epoch. The cumulative sleep index (CSI) is the integral of sleep suppression across recording time thereby reflecting both the duration and depth of sleep over specified intervals (higher value is deeper and longer sleep). 36 patients with long sleep (600 minutes or longer) recorded through unconstrained polysomnography were analyzed using ORP across the full study (12.7±1.7 hours). Participants were divided into quartiles, 9 patients each(Q1-Q4) based on accumulated sleep across the entire study. Results: The mean age for the cohort was 35.8 ± 16.2, of which 29/36 were females. Total sleep time by visual scoring was 679.4 ± 96.4 minutes (range: 601.5 - 1145) minutes). The whole night CSI mean was 989.39 ± 271.64 units (range: 345 to 1427). The quartile values were 618.33 ± 178.83, 919.33 ± 67.27, 1142.89 ± 39.01, and 1277 ± 69.39 units, and not related to total recording or sleep time. The NREM sleep ORP was 1.43± 0.32, 1.06 ± 0.22, 0.73± 0.13 and 0.67 ± 0.19, respectively. This distribution was true for REM sleep ORP also: 1.52 ± 0.30, 1.26 ± 0.19, 1.05 ± 0.25, and 0.84 ± 0.21, respectively. The trait-like ORP-9 (9 seconds post-arousal), and a reflection of sleep fragmentation propensity, was also similarly distributed: 1.60 ± 0.30, 1.29 ± 0.27, 0.92 ± 0.15, and 0.80 ± 0.18, respectively. All comparisons were statistically significant by Tukey multiple comparisons. Conclusion: Patients with IH are not homogenous, showing a range of sleep depth in both NREM and REM sleep regardless of total sleep time. These phenotypes of IH could reflect unique endotypic mechanisms, requiring different therapies or have differential treatment responses. Support (If Any):